Ribosomal RNA metabolism in cucumber leaf mesophyll protoplasts. - Coutts, R H (1975)
Aspects of the metabolism of RNA have been studied in enzymatically isolated protoplasts from cotyledon and first leaf mesophyll tissue of two cultivars of cucumber. The first leaf mesophyll protoplasts incorporated (3H)-uridine into ribosomal RNA at a constant rate for up to 25 hr in a simple salts medium and for up to 45 hr in a growth medium. Pulse-chase labelling experiments on such preparations showed a rapid dilution of the intracellular (3H)-uridine pool(s) and a high metabolic rate in the cells in one cultivar but not in another. Gel electrophoretic analysis of the RNA from both cotyledon and first leaf protoplasts showed that both protoplast types incorporated either (14C)- or (3H)-uridine into ribosomal RNA species. Incorporation of (3H)-uridine into chloroplasts RNA was minimal in cotyledon protoplasts, but significant in leaf protoplasts. Greater incorporation into the chloroplast RNA species could be achieved by longer pulses. Synthesis of all of the ribosomal RNA species was sensitive to actinomycin D at 10 and 25 mug/ml concentrations in all protoplasts tested.